PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN MELALUI LIKUIDITAS PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kalsum, Ummu; Asdar, Muh.; Nursafitrah, Nursafitrah (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of capital structure on the financial performance of companies in the food and beverage industry sector listed on the Indonesia Stock Exchange (IDX), with liquidity as a mediating variable. Companies in this sector face challenges in maintaining good financial performance amid intense market competition. Therefore, understanding the role of capital structure and liquidity in influencing financial performance is essential. The research method used is a quantitative approach with secondary data obtained from the financial reports of companies listed on the IDX for the 2022–2024 period. The analysis technique employed is simple linear regression to examine the influence between the independent variable (capital structure) and the dependent variable (financial performance), mediated by liquidity. The results of the study show that capital structure has a positive and significant effect on liquidity, and liquidity also has a positive and significant effect on financial performance. Capital structure also has a direct and significant influence on financial performance. However, based on the Sobel test results, it was found that liquidity does not significantly mediate the effect of capital structure on financial performance.